2016
DOI: 10.4209/aaqr.2015.05.0298
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Looping Gasification of Charcoal with Iron-Based Oxygen Carriers in an Annular Dual-Tube Moving Bed Reactor

Abstract: Charcoal used as solid fuel for chemical looping gasification (CLG) with Fe 2 O 3 /Al 2 O 3 oxygen carriers was investigated in an annular dual-tube moving bed reactor (ADMBR). Pure CO 2 and steam/CO 2 mixture were used to gasify the charcoal in a fixed bed reactor. More combustible gases, CO and H 2 , were observed in the outlet gas streams for charcoal gasification conducted with steam/CO 2 mixture than those with only CO 2 . The yields of fuel gases were determined to modify the equation of oxygen carrier-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Luo et al (2014b) indicated that the kinetic of charcoal gasification was enhanced by increasing the flow rate of the gasification agent. More H 2 O and CO 2 were produced from fuel gases combustion and was subsequently reacted with charcoal to perform gasification reaction, consistent with the results found in the literatures (Fan, 2010;Wu and Ku, 2016). However, the carbon conversions were found to be diminished by the addition of excessive steam (> 221.4 mmol min -1 ).…”
Section: Clc Of Charcoal By Fesupporting
confidence: 88%
See 1 more Smart Citation
“…Luo et al (2014b) indicated that the kinetic of charcoal gasification was enhanced by increasing the flow rate of the gasification agent. More H 2 O and CO 2 were produced from fuel gases combustion and was subsequently reacted with charcoal to perform gasification reaction, consistent with the results found in the literatures (Fan, 2010;Wu and Ku, 2016). However, the carbon conversions were found to be diminished by the addition of excessive steam (> 221.4 mmol min -1 ).…”
Section: Clc Of Charcoal By Fesupporting
confidence: 88%
“…Charcoal is a promising solid fuel due to its lower moisture content, higher calorific value, lower tendency to biodegradation, and easy to pulverize like coal (Gucho et al, 2015;Strandberg et al, 2015). Wu and Ku (2016) indicated that the maximum fuel conversion and oxygen carrier conversion for chemical looping gasification (CLG) of charcoal with Fe 2 O 3 /Al 2 O 3 oxygen carrier were found to be 11.5% and 38.3%, respectively, and also reported that more syngas (CO/H 2 ) were generated for charcoal gasification conducted in the moving bed reactor operated with higher oxygen carrier-to-fuel ratios.…”
Section: Introductionmentioning
confidence: 99%
“…IPA conversion (XIPA) and oxygen carrier conversion (XOC) for IPA combustion were determined by Eqs. ( 8) and ( 9) (Zeng et al, 2015;Wu and Ku, 2016). The detailed mass balance data of the IPA combustion experiment, such as oxygen, carbon, hydrogen, and iron, were listed in Table 2.…”
Section: Ipa Combustion With Fabricated Fe2o3/al2o3 Oxygen Carriers In the Admbrmentioning
confidence: 99%
“…[ 87 ] The loss of OCs' surface areas is commonly attributed to sintering and agglomeration. [ 60,214 ] However, in specific cases, for example, CuFe 2 O 4 , [ 87 ] CuO supported on olivine [ 97 ] and Fe 2 O 3 supported on Al 2 O 3 , [ 55 ] oxygen carriers gain additional surface areas after chemical looping cycles. This phenomenon originates from the generation of additional porosity inside the OC particles over repeated redox cycles.…”
Section: Operando Characteristics Of Oxygen Carriersmentioning
confidence: 99%